Il metodo impuro nel Capitale di Marx - Tomba, Massimiliano (Bollettino Filosofico, 2025)
Marx’s Capital offers an impure method based on three dimensions or facet analysis. The first facet is conceptual, presenting the Critique of Political Economy as an immanent critique of the concepts of classical economics, even going so far as to reveal the “inversion” between values and exchange values, along with the social form corresponding to this inversion. The second dimension is ethnographic and historical. Here, Marx descends into the laboratories of production to show how surplus value is extracted and how workers, along with their labor, are exploited and consumed. In this second level, the inversion appears as “perversion”. This level is not deducible from the first; here, dialectics gives way to history, and Hegel gives way to Horner. The third dimension concerns class struggle and workers’ attempts to give shape to a social form liberated from exploitation. This is what Marx calls the Political Economy of the Working Class. It represents a rise from the horrors of production and the anticipation of a different form of life. Each of these facets casts a different light on the analysis. Considering only one perspective risks becoming one-sided and abstract, losing sight of the political and historical dimension’s concreteness, which instead emerges from the interplay of all three dimensions. Keywords: Capital, Exploitation, Factory Reports, History, Impure Method, Karl Marx